Transformasi Ancaman Bioterorisme: Serangan Ricin 2020 dan Tantangan Penanggulangan dalam Ancaman Keamanan Biologis - Nurul Deswita Iqbal; Imam Fadhil Nugraha (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Historically, bioterrorism has been framed as a form of violence with mass casualty associated with state-level actors, advanced laboratory infrastructure, and use of Weapons of Mass Destruction (WMD). However, with rapid developments in biotechnology, and open-access scientific knowledge have fundamentally transformed the landscape of this threat. This article argues that bioterrorism has gone through a structural transformation from a state-centric, centralized, WMD paradigm toward a more decentralized, individually based form and conceptualised in this article as micro-bioterrorism. Through comparative case study analysis spanning from the 1984 Rajneeshee salmonella attack, the 1993-1995 Aum Shinrikyo biological weapons program, the 2001 United States anthrax attacks, and recent contemporary individual-actor incidents such as the 2018 Cologne incident and the 2020 Ricin attack attempt targeting the White House, this article examines the mechanisms factoring this transformation. Ricin emerges as a recurring indicator of this shift due to its accessibility and the widespread availability of operational knowledge. Through Critical Security Studies (CSS) and Michel Foucault’s Biopolitics this article will evaluate its theoretical foundations, and the limitations of the Biological Weapons Convention (BWC) in addressing non-state, individual actor threats. This article concludes that existing biosecurity governance frameworks remain structurally misaligned with the decentralized nature of contemporary biological threats, requiring a fundamental reconceptualization of biosecurity surveillance, governance architecture, and international cooperation.